WHICH IS MORE RELATED TO LITERACY SKILLS, COMPETITION OR COOPERATION? EVIDENCE FROM PISA 2018 RESULTS - Rasmuin Rasmuin (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Although previous research has demonstrated that school climate (leading to a climate of competition or cooperation) is related to student achievement, including their literacy skills, there is still insufficient evidence which of the two school climates is more related to literacy skills. Therefore, this study examined the relationship between the two sets of variables in the PISA 2018 Results data: students’ perceptions of school climate (PERSCHL) and literacy skills (LITERACY). The PERSCHL set consists of perceptions of the level of competition (PERSCOMP) and cooperation (PERSCOOP) in schools, while LITERACY set consists of mathematical literacy (MATH), reading (READ), and science (SCIE). The research was conducted to answer the questions: (1) is there a relationship between a student’s perception of competition and cooperation with students’ literacy skills? and (2) which one of the two PERSCHL variable sets has the most influence on students’ literacy skills? The level of perception in the PERSCHL set was estimated using the Graded Response Model (GRM), while literacy skills was calculated from the average of 10 Plausible Value (PV) that has been available in the data of PISA 2018 Results. The research hypothesis was tested using canonical correlation analysis. The results of the data analysis showed that the positive students’ perceptions of competitive and cooperative school climate had a positive and significant association with literacy skills although with a small correlation index. Second, perceptions of competition have a higher relationship with literacy skills than perceptions of cooperation in schools but the difference between the two is small. Both competition and cooperation in schools still need to be developed to facilitate the improvement of student literacy skills individually and collectively.